2002
DOI: 10.1038/ni778
|View full text |Cite
|
Sign up to set email alerts
|

Tracing lymphopoiesis with the aid of a pTα-controlled reporter gene

Abstract: A transgenic reporter mouse strain, which expressed the human CD25 (hCD25) surface marker as a reporter under the control of the pre-T cell receptor alpha(pTalpha) promoter, was used to identify lymphoid precursors that expressed pTalpha intracellularly. The hCD25 reporter marked intra- and extrathymic precursors of lymphocytes but not myeloid cells. The earliest intrathymic precursors were CD4(lo)CD8(-)CD25(-)CD44(+)c-Kit(+) cells that expressed elevated levels of Notch-1 mRNA. Clonogenic assays showed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 42 publications
8
70
0
Order By: Relevance
“…Interestingly, the endogenous TCRb locus was allelically excluded in such cd cells in all three TCRb Tg lines, and this allelic exclusion could be reversed in the absence of pTa. These data provide direct functional evidence that pTa is expressed in precursors of cd cells, confirming and extending earlier studies of ic pTa [6] and pTa reporter gene expression [20] in immature DN3 thymocytes. Thus, models of ab/cd lineage commitment that propose a restricted expression or function of pTa in the ab lineage [34,35] are clearly oversimplified.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, the endogenous TCRb locus was allelically excluded in such cd cells in all three TCRb Tg lines, and this allelic exclusion could be reversed in the absence of pTa. These data provide direct functional evidence that pTa is expressed in precursors of cd cells, confirming and extending earlier studies of ic pTa [6] and pTa reporter gene expression [20] in immature DN3 thymocytes. Thus, models of ab/cd lineage commitment that propose a restricted expression or function of pTa in the ab lineage [34,35] are clearly oversimplified.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies using pTa ic staining [6], single-cell PCR [19] and reporter mice [20] are consistent with the possibility that most DN3 thymocytes, which have recently been shown to contain a very small subset of cd precursors [21], express pTa. However, no functional evidence for the presence of pTa in cd precursors has been reported.…”
Section: Tcrb Transgenes Mediate Pta-dependent Allelic Exclusion In Csupporting
confidence: 60%
“…It has recently been suggested that B220 ϩ CD19 Ϫ pre-TCR␣ gene (pT␣) ϩ progeny of CLPs, termed CLP-2s, may seed thymus (43,44). Cells with a CLP-2 phenotype can be identified in the thymic DN1 compartment of pT␣ reporter mice, but appear considerably less efficient than ETPs in their T lineage potential (44).…”
Section: Cells (42) An Examination Of Early Progenitors In Ikarosmentioning
confidence: 99%
“…In addition to jejunum and thymus, pT␣ a mRNA was also detected in mononuclear cells of bone marrow and blood. In a mouse strain with human CD25 as a pT␣-controlled reporter gene, it was recently shown that the bone marrow harbors the CD19 Ϫ lymphoid precursor that expresses pT␣ mRNA (41). However, these cells were not committed for development into ␣␤ T cells and pT␣ was even expressed before onset of TCR gene rearrangement.…”
Section: Cd3mentioning
confidence: 99%